526 Barriers to Effective Clinical Research Professional (CRP) Education and Competency Development: A Qualitative Analysis of Data from a National UnMeeting Series. (April 2022) - Kolb, H. Robert; Freel, Stephanie; Fritter, Jessica; Helm, Shirley; Jenkerson, Michelle; Jester, Penelope; Jones, Carolynn; Mendell, Angela; Petty, Megan; Tsao, Peg
Abstract : OBJECTIVES/GOALS: a. Summarize barriers and best practices related to effective CRP onboarding, training and professional development b. Identify challenges with the assessment of and mentoring for CRP competency growth. c. Describe opportunities to improve the training and professionalization of the CRP career pathway. METHODS/STUDY POPULATION: Qualitative data from a series of UnMeeting breakout sessions and open-text survey questions were analyzed to explore the complex issues at play when developing high-quality onboarding and continuing education opportunities for CRPs at academic health centers. RESULTS/ANTICIPATED RESULTS: Results suggest there are several barriers to providing training to the CRP workforce, including: balancing foundational onboarding with role-based training, managing logistical challenges and institutional contexts, the need for institutional champions, assessing competency, and providing high-quality mentorship. Several of these themes are interrelated. One common thread present throughout all of these themes is the challenge of effective communication and team science training. DISCUSSION/SIGNIFICANCE: Few institutions have solved all of the issues related to training a competent and adaptable CRP workforce, although some have addressed one or more. This study illustrates the need to work collaboratively within and across institutions to overcome training barriers and support a vital and well-qualified workforce.